Karte von dem ostlichen-stucke von Neu Frankreich oder Canada - Bellin, Jacques Nicolas, 1703-1772 ([Leipzig], 1756)
Black and white. Prime meridian Paris. North arrow. Relief shown pictorially and by soundings. Shows underwater features. Bar scales in ordinary, French and English sea nautical miles. Includes note.